Pengembangan Media Pembelajaran dengan Metode Lagu pada Materi Sifat Huruf Hijaiyah di TPA Walisongo Singopuran Kartasura - Anisah Dwi Lathifah; Serly Tiara Amani Zulfa; Awalia Khalifatur Riska; Asma Laili Hanifah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This research is based on the observations and experiences of researchers that many teachers still do not use media in learning activities, especially in the material on the nature of hijaiyah letters. This condition causes students to not understand and not master the material about the nature of the hijaiyah letters. This research aims to develop learning media in the form of songs on the material of the nature of hijaiyah letters. Furthermore, the purpose of this study was to determine the validity, practicality, and effectiveness of the song learning method on the material of the nature of hijaiyah letters at the TPA Walisongo Singopuran Kartasura Mosque. This research applies a qualitative approach, the main techniques in collecting data include documentation, observation, interviews and tests. It is hoped that the results of this study can contribute to the development of more innovative and interesting learning methods, especially in learning the nature of hijaiyah letters. (1) Development The song method is an effective approach in improving the learning outcomes of hijaiyah letter traits in students at TPA Masjid Walisongo Kartasura Mosque. (2). There are 80% of students who feel helped and easier to easier to understand the material with the use of the song method. (3) Song method can be an interesting alternative for interesting alternative for teachers to build learning the nature of hijaiyah letters that are more ineractive, fun, and effective. ineractive, fun, and effective.